2018
DOI: 10.1073/pnas.1720833115
|View full text |Cite
|
Sign up to set email alerts
|

Role of glutathione metabolism in host defense against Borrelia burgdorferi infection

Abstract: Pathogen-induced changes in host cell metabolism are known to be important for the immune response. In this study, we investigated how infection with the Lyme disease-causing bacterium () affects host metabolic pathways and how these metabolic pathways may impact host defense. First, metabolome analysis was performed on human primary monocytes from healthy volunteers, stimulated for 24 h with at low multiplicity of infection (MOI). Pathway analysis indicated that glutathione (GSH) metabolism was the pathway mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 36 publications
3
43
2
Order By: Relevance
“…This enzyme is present in B. burgdorferi OMVs, making it a prime candidate for modulation of host cell superoxide levels [18]. Past studies have shown that B. burgdorferi can reduce peripheral blood mononuclear cell ROS levels in response to ROS-generating stimuli, while at the same time showing a decrease in intracellular superoxide [55]. In the same study, it was found that the decrease in superoxide was independent of mammalian antioxidants, namely glutathione.…”
Section: Discussionmentioning
confidence: 95%
“…This enzyme is present in B. burgdorferi OMVs, making it a prime candidate for modulation of host cell superoxide levels [18]. Past studies have shown that B. burgdorferi can reduce peripheral blood mononuclear cell ROS levels in response to ROS-generating stimuli, while at the same time showing a decrease in intracellular superoxide [55]. In the same study, it was found that the decrease in superoxide was independent of mammalian antioxidants, namely glutathione.…”
Section: Discussionmentioning
confidence: 95%
“…Glutathione and alkalizing the body to decrease acidic byproducts has been shown to be helpful in decreasing symptomatology in this population of patients [57]. Glutathione metabolism has also been discovered to be the most important target of B. burgdorferi infection, and this pathway is essential for cytokine production, likely through glutathionylation [58]. Glutathione and GSH precursors (NAC) with antioxidants that help regenerate GSH (alpha lipoic acid) have been an effective mainstay of treating cytokine storms and Herxheimer reactions in our tick-borne population for decades [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione modulates inflammation [172,173]. A 2018 PNAS report found that intracellular GSH production was increased up to 10-fold during an infection with Borrelia burgdorferi , and infection was a key factor in inflammation/cytokine production [174]. Glutathione is also a key factor in helping to detoxify environmental chemicals.…”
Section: Discussionmentioning
confidence: 99%